EXAMINING CULTURAL APPEALS IN PERSUASIVE AUDIO AND VIDEO MATERIALS - Sinta Uli Simbolon; Angelina Merici Wua Reku; Zahwa Amelia Putri Dermawan; Ni Nyoman Sarmi; Cahyaningsih Pujimahanani; Rommel Utungga Pasopati (STKIP Citra Bakti, 2026)
This study explores the role of cultural appeals in shaping persuasive communication in audio and video media. Cultural appeals refer to the use of shared values, beliefs, traditions, and social norms to influence audience perception and behavior. Grounded in communication and cultural studies, this research explores how cultural references are embedded in both audio formats, such as podcasts and radio, and video formats, including advertisements and digital media content. In audio media, cultural appeals are often conveyed through language choice, storytelling, accents, and culturally specific narratives that resonate with listeners’ identities and experiences. In contrast, video media incorporate visual symbols, settings, clothing, and gestures that more explicitly represent cultural contexts and enhance audience recognition. Using a comparative analytical approach, this study evaluates selected audio and video samples to identify how cultural elements are emphasized and interpreted across different media. The findings suggest that while both formats effectively employ cultural appeals, video media provide a more immediate and vivid representation of cultural identity, whereas audio fosters deeper personal interpretation and imagination. In conclusion, this study contributes to the understanding of persuasive communication by highlighting the importance of cultural sensitivity and relevance, offering practical insights for content creators aiming to engage diverse audiences effectively.